13. SATISFACTION OF PATIENT/PATIENT'S FAMILY WITH NURSING CARE AT THE DEPARTMENT OF COSMETIC SURGERY OF HANOI MEDICAL UNIVERSITY HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the satisfaction of patients and patients’ families with nursing care at the cosmetic plastic surgery department of Hanoi Medical University Hospital in 2023. Subjects and methods: A cross-sectional descriptive study was conducted on 132 research subjects who were patients or family members directly taking care of patients from June 2023 to December 2023. Results: Research shows 89,4% Patients/patients’ families are generally satisfied with nursing care. All factors have a high satisfaction rate of over 90%, of which the factor “Nurses’ attitude and communication skills” has the highest satisfaction rate of 97.7%. The lowest satisfaction is “Administrative procedures” with a rate of 92.4%. Up to 97% of patients/patients’ families agreed to return or recommend friends to the hospital, and 93,4% agreed to continue for follow-up examinations and treatment at the Department of Aesthetic Plastic Surgery, Hanoi Medical University Hospital. Conclusions: In general, the satisfaction with nursing care of patients/patients’ families at the Department of Aesthetic Plastic Surgery at Hanoi Medical University Hospital is quite high. In addition, nurses need to guide patients through administrative procedures and arrange procedures for patients to be quick and easy to understand.
Keywords: Satisfaction; patients, patients’ families; Department of Aesthetic Plastic Surgery.